Can increased glacial melting resulting from global change provide attached algae with transient protection against high irradiance? - Martyniuk, Nicolás Alejandro (2014)
Climate change is altering temperatures and precipitation patterns all over the world. Melting glaciers increase surface run-off, thereby increasing the transport of suspended solids through streams. The increased load of suspended solids affects turbidity, which decreases the availability of photosynthetically active radiation for primary producers. 2. We analysed how glacial loading of clays influences the light : nutrient ratio and photosynthetic parameters (measured with a pulse amplitude modulated fluorometer) and the carbon : phosphorus (C : P) elemental ratio of periphytic primary producers. A field study was conducted in two canopyfree streams that receive water from the glaciers of Mount Tronador (Patagonia, Argentina), one with high glacial load and the other with clear water. In addition, we conducted an in situ colonisation experiment with three different light treatments. 3. We observed that periphytic biomass (chlorophyll a and carbon content) in the streams and in the experiment varied directly with turbidity. Moreover, photosynthetic parameters varied similarly because of an increase in the efficiency of electron transfer per open reactive centre in the more turbid stream and a chronic photoinhibition of photosystem II in the clearer stream. 4. Periphytic C : P also varied with turbidity as we observed a decrease in C : P with an increase in light in both streams and in the experiment. 5. Our main conclusion is that an increase in glacial melting with its associated increase in glacial clay load should protect primary producers against high irradiances (photosynthetic active radiation + ultraviolet radiation) in canopy-free streams.